Impacts of Ethnic Conflict on Micro-Entrepreneurship in Manipur - Devi, Laishram Jeena; Singh, Khumukcham Tomba (AMC Indian Journal of Entrepreneurship, 2024)
Purpose : The present study aimed to analyze the impacts of an ongoing violent conflict on micro-entrepreneurship in Manipur, one of the northeastern states of India. On May 3, 2023, hostilities broke out between the state’s two largest communities. The study examined how the entrepreneurs dealt with the crisis, in addition to highlighting the difficulties and problems they encountered. Methodology : The study adopted a qualitative approach by using an explorative research design to understand in depth the situation of the entrepreneurs and their businesses that were caused by the conflict. Three cases of micro-based entrepreneurial units were deeply studied by using a semi-structured interview guide. Findings : All three business ventures were financially affected by prolonged lockdowns, curfews, cancellation of transportation, infinite internet shutdowns, and violence. A conceptual model was used to analyze the data, showing how the crisis affected the company’s capacity to sell its goods, as well as how much labor, raw materials, and other costs were and how quickly they could be produced. These immediate impacts on businesses further affected the entrepreneurs financially, psychologically, and socially. However, their interpretation and understanding of the overall impacts of the crisis on the entrepreneurs as well as their businesses were subjective and influenced how they reacted. According to the entrepreneurs’ interpretation, they adopted coping strategies and responded to the conflict. The entrepreneurs responded in a variety of ways, such as positively, adversely, and passively or actively. Such a crisis’s micro-level effects affected its macro-level effects. Practical Implications : The study discussed how conflicts impact micro-entrepreneurs’ circumstances. Policymakers and other relevant stakeholders will benefit from having a better knowledge of the unique vulnerabilities and problems faced by micro-entrepreneurs in Manipur today. This academic contribution would be helpful for various organizations and civil societies in establishing partnerships, public platforms, and network formation among various stakeholders of the society, including entrepreneurs. Originality : The current study’s findings, which are heavily impacted by the ongoing violent conflict, were used to identify potential policy and intervention approaches for entrepreneurship and rehabilitation in the state.